2014
DOI: 10.2337/db13-1100
|View full text |Cite
|
Sign up to set email alerts
|

Epigenome-Wide Association Study of Fasting Measures of Glucose, Insulin, and HOMA-IR in the Genetics of Lipid Lowering Drugs and Diet Network Study

Abstract: Known genetic susceptibility loci for type 2 diabetes (T2D) explain only a small proportion of heritable T2D risk. We hypothesize that DNA methylation patterns may contribute to variation in diabetes-related risk factors, and this epigenetic variation across the genome can contribute to the missing heritability in T2D and related metabolic traits. We conducted an epigenome-wide association study for fasting glucose, insulin, and homeostasis model assessment of insulin resistance (HOMA-IR) among 837 nondiabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
140
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 32 publications
(43 reference statements)
7
140
2
Order By: Relevance
“…The protocol was approved by the Institutional Review Boards of University of Minnesota, University of Utah, Tufts University/New England Medical Center, and the University of Alabama at Birmingham. More details about the GOLDN study have been published in earlier reports [17][18][25][26][27]. Baseline and postfenofibrate intervention data were available for 750 participants with DNA methylation measurements.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol was approved by the Institutional Review Boards of University of Minnesota, University of Utah, Tufts University/New England Medical Center, and the University of Alabama at Birmingham. More details about the GOLDN study have been published in earlier reports [17][18][25][26][27]. Baseline and postfenofibrate intervention data were available for 750 participants with DNA methylation measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Random subsets of 10,000 CpGs per run were run after normalization, in which each array of 12 samples were used as batch. Correction for differing probe chemistry was performed on Illumina Infinium HumanMethylation450 Bead chip, normalizing the probes separately from the Infinium I and II [26][27]29,31].…”
Section: Estimation Of Dna Methylationmentioning
confidence: 99%
“…7 Interestingly, a recent epigenome-wide association study among 837 nondiabetic participants in the Genetics of Lipid Lowering Drugs and Diet Network study suggested that cytosine guanine dinucleotide (CpG) methylation at CpG sites in ABCG1 locus in CD4C T cells was significantly associated with insulin levels and HOMA-IR. 8 Those latter studies would suggest that pharmacological inhibition of ABCG1 could exert potentially deleterious effects on insulin resistance (IR), This possibility is however weakened by the observation that Abcg1 -/-mice fed a highfat diet did not exhibit glucose intolerance or liver steatosis, in contrast to control Abcg1 C/C littermates 4 , suggesting that total Abcg1 deficiency should rather protect against IR rather than deteriorate it. However, our analysis of ABCG1 SNPs in 1320 morbidly obese patients revealed that both rs1378577 and rs1893590 were not associated with HOMA index independently of BMI.…”
mentioning
confidence: 93%
“…Low amounts of membrane SM ensures optimal LPL activity and hydrolysis of triacylglycerol-rich lipoproteins (TRL) (3), contributing to the release of free fatty acids (FA) (4). Released FFAs are then taken up by the cell (5) and used for triglycerides synthesis (6), leading to TG storage (7) and to increased lipid droplet size in adipocytes (8). Optimal LPL activity is also accompanied by TRL uptake, ensuing increase of intracellular cholesterol content (5).…”
mentioning
confidence: 99%
“…The first T2D epigenome-wide association studies (EWASs) are now starting to be performed (Dick et al 2014, Hidalgo et al 2014, Petersen et al 2014, Chambers et al 2015, Kulkarni et al 2015. However, so far, T2D EWAS have only been performed with wholeblood cells instead of pancreatic islets or other diseaserelevant tissues, only being able to grasp early developmental epigenetic changes, which can be present in multiple tissues, and alterations derived from inflammatory processes, which are often detectable in circulating blood.…”
Section: Next Challenges For T2d Variant Discoverymentioning
confidence: 99%